2007
DOI: 10.1038/laban0407-29
|View full text |Cite
|
Sign up to set email alerts
|

Use of the laryngeal mask airway in rabbits: placement and efficacy

Abstract: The laryngeal mask airway (LMA) has been used in various animal species anesthetized for the purpose of device evaluation, but the device has not been evaluated in rabbits during surgery. The authors tested the feasibility and potential advantages of using the LMA in 50 rabbits undergoing surgery under spontaneous-breathing inhalational anesthesia, focusing mainly on the technique of insertion and its efficacy. The LMA was easily inserted and no air leakage at the larynx was detected. Although four rabbits dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…A similar phenomenon was described by Kazakos and others (2007) in 4 out of 50 rabbits. It was attributed to vascular compression at the basis of the tongue by the LM.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar phenomenon was described by Kazakos and others (2007) in 4 out of 50 rabbits. It was attributed to vascular compression at the basis of the tongue by the LM.…”
Section: Discussionsupporting
confidence: 85%
“…In several animal species as in humans, the use of a LM for airway management is described as easy, simple and rapid (Benumof 1992, Wemyss-Holden and others 1999, Kazakos and others 2007, Wiederstein and Moens 2008). This is also the case in adult (Goldmann and others 2005) and neonatal (Roberts and others 2010) pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Lingual cyanosis has been noted in rabbits with laryngeal masks, probably due to device pressure on lingual vasculature (Kazakos and others 2007). …”
mentioning
confidence: 99%
“…Studies have shown that LMAs in rabbits were easy to insert, but they had the potential of causing lingual cyanosis, gastric tympany, laryngeal oedema and air leak around the cuff (Bateman and others 2005, Kazakos and others 2007, Uzun and others 2015). These studies utilised an LMA that was specifically designed for human oropharyngeal anatomy.…”
Section: Introductionmentioning
confidence: 99%